Energy and protein requirements of male and female saanen goats - Figueiredo, Fernanda Oliveira de Miranda [UNESP] (2014)
The objective of this research was to estimate, using the comparative slaughter technique, energy and protein requirements for maintenance and growth of castrated males, intact males and females Saanen goat kids between 15 and 30 kg of body weight and to evaluate the models from AFRC (1998) and NRC (2007) for predicting dry matter intake (DMI) and average daily gain (ADG) of growing goats. To determine net energy and net protein requirements for maintenance 25 castrate males, 26 intact males and 24 females were used, where 7 castrated males, 8 intact males and 6 females were randomly selected to estimate the initial empty body composition. The remaining animals, 18 castrate males, 18 intact males, and 18 females were used with dietary treatments that consisted of 3 levels of intake: ad libitum, 75% and 50% of ad libitum intake. Within each sex, six blocks of 3 animals each were formed. Within each block, one animal was randomly assigned to each level of intake. Thus, pair feeding was established within each block based on the intake of the animal fed ad libitum. All animals within a block were slaughtered when the animal fed ad libitum reached 30 kg of BW. The 75 and 50% of ad libitum rationing were determined daily based on the DMI of the animal fed ad libitum on the previous day. The net energy and net protein requirements for gain (NEg and NPg, respectively) were obtained using 20 castrated males, 20 intact males and 18 females. The animals were fed ad libitum and slaughtered at targeted BW of 15, 23, and 30 kg. We found that sex did not affect energy and protein requirements for maintenance as well as protein requirements for growth. However it affected energy requirements for growth where castrated males and females had the same NEg comparing with intact males. To evaluate the models from AFRC (1998) and NRC (2007) for predicting DMI and ADG of growing goats, individual data of 37 Saanen goat kids (12 intact males, 13 castrated ...